Formulation, optimization and evaluation of sustained release microsphere of ketoprofen - V Chirag Prajapati; P Rakesh Patel; G Bupendra Prajapati (Wolters Kluwer Medknow Publications, 2012)
The objective of this study is to formulate ketoprofen loaded microspheres of Acrycoat S100 by an o/w emulsion solvent evaporation method. It potently inhibits the enzyme cyclooxygenase resulting in prostaglandin synthesis inhibition. Ketoprofen causes an irritation in the gastrointestinal mucous membrane and possesses a bitter taste and aftertaste. The half-life in plasma is about 1-2hrs. This makes ketoprofen a very good candidate for the formulation of controlled release dosage forms. Ketoprofen microspheres help to protect the gastric mucous membrane from drug irritation and to mask its taste. The prepared microspheres were evaluated for micromeritic properties, particle size, effect of surfactant concentration, percentage yield, incorporation efficiency, drug polymer compatibility (IR and DSC study), scanning electron microscopy and in vitro drug release. The microspheres produced exhibited good encapsulation efficiencies and micromeritic properties. Encapsulation efficiency of microsphere is around 78%. The mean diameters of microspheres were found in required micrometer range. The results of optimized formulations showed a narrow size distribution and smooth surface. The DSC and the FTIR analysis showed the absence of any potent incompatibility between the drug and the polymer. In-vitro release showed 86.4% drug release after 12 hours. Results of present study suggest that Acrycoat S100 loaded microsphere of ketoprofen can be successfully designed to develop sustained drug delivery system. The solvent evaporation method is a suitable technique for the preparation of Acrycoat S100 microspheres for controlling the release of Ketoprofen for a prolonged duration.